Evaluation of endosonography in TN staging of oesophageal cancer. Issue 1 (January 1991) - Ziegler, K; Sanft, C; Zeitz, M; Friedrich, M; Stein, H; Häring, R; Riecken, E O
Abstract : Strategies for the treatment of cancer of the oesophagus depend on the tumour stage at the time of diagnosis. Resection, the only curative treatment, is confined to early tumour stages. Tumours with local infiltration are usually unresectable and require palliative treatment. Computed tomography has been widely used for preoperative staging but often fails to define this correctly. Endoscopic ultrasound allows direct visualisation of the parietal wall and may be useful in staging gastrointestinal tumours. In a comparative prospective study, 52 patients with tumours of the oesophagus were investigated preoperatively both by endoscopic ultrasound and computed tomography to determine the stage of tumour infiltration and local lymph node involvement. Thirty seven of these patients underwent operation, resection, or dissection and entered the study. The intraoperative findings or the histopathological assessment, or both, were taken as a reference. For all TN stages of oesophageal tumours, correct preoperative staging was accomplished by endoscopic ultrasound in 89% for T stage and 69% for N stage compared with 51% and 51% respectively by computed tomography (highly significant using Fisher's exact test). This study shows that endoscopic ultrasound is useful in preoperative TN staging of tumours of the oesophagus.